2019
DOI: 10.1016/j.gendis.2019.06.001
|View full text |Cite|
|
Sign up to set email alerts
|

A novel inhibitor of MDM2 oncogene blocks metastasis of hepatocellular carcinoma and overcomes chemoresistance

Abstract: Overexpression of the MDM2 oncogene and mutations in the p53 tumor suppressor commonly occur in hepatocellular carcinoma (HCC) and are associated with increased mortality due to this disease. Inhibiting MDM2 has been demonstrated to be a valid approach for the treatment of HCC. However, most of the MDM2 inhibitors evaluated to date have been designed to block the MDM2 and p53 binding, and have limited efficacy against tumors with mutant or deficient p53. In the present study, we developed a novel MDM2 inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
86
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(90 citation statements)
references
References 34 publications
4
86
0
Order By: Relevance
“…Moreover, studies found that MDM2 may suppress the migration of cancer cells and could induce apoptosis [27,29,30]. Our results found that BBM inhibited the migration and invasion of A549 cells in vitro, and the number of nodules on lungs was signi cantly reduced in vivo, and the expression of MDM2 was downregulated both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…Moreover, studies found that MDM2 may suppress the migration of cancer cells and could induce apoptosis [27,29,30]. Our results found that BBM inhibited the migration and invasion of A549 cells in vitro, and the number of nodules on lungs was signi cantly reduced in vivo, and the expression of MDM2 was downregulated both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 52%
“…In addition, Zhang et al found that p53 and MDM2 expression levels could be considered as useful indicators for predicting the prognosis of HCC [28]. Furthermore, MDM2 knockdown has also been demonstrated to inhibit cancer cell growth and invasion, induce apoptosis, and sensitize HCC cells to sorafenib [29]. Unfortunately, the specific targets of circRNAs regulation in sorafenib resistance HCC remain unknown and further in vitro and in vivo studies are needed to fully reveal the differentially expressed circRNAs and their underlying mechanisms, which may be useful for HCC therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Scratches were made at experimental time zero and then the cells were exposed to varying concentrations of SP-141. The wells were photographed at different time points and the migration was quantified [ 30 , 31 , 32 ]. Transwell invasion assays were performed by exposing tumor cells to SP-141 for 24 h, and the cells that migrated into the lower chambers were stained with crystal violet [ 30 , 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Following NaBH 4 reduction, cells were blocked, treated with corresponding antibodies in the presence of 0.2% Triton X-100, then incubated with FITC-conjugated secondary antibodies. The washed cells were analyzed by flow cytometry [ 30 , 31 , 32 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation